Biochemical and Physiological Insights into Adipokine-Mediated Insulin Resistance and Its Association with Atherosclerotic Progression in Prediabetic Patients - Nishat Afroz, Humera Khan, Kahkashan Perveen, Sumaira Deen Muhammad, Mumtaz Lakho, Azhar Ijaz, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Prediabetes is a metabolically active state associated with insulin resistance and early vascular dysfunction, serving as a precursor to type 2 diabetes mellitus (T2DM) and atherosclerotic cardiovascular disease. Adipokines bioactive molecules secreted by adipose tissue are central to this progression, yet their role in prediabetic individuals remains under-investigated. Objective: To assess the biochemical and physiological roles of adipokines adiponectin, leptin, resistin, and visfatin in mediating insulin resistance and their association with subclinical atherosclerosis in prediabetic patients. Methods: This cross-sectional study was conducted from November 2022 to May 2023 at Shahbaz Sharif Hospital, Multan, and Bolan Medical Complex Hospital (BMCH), Quetta. A total of 100 prediabetic individuals (aged 30–60 years) were enrolled. Fasting glucose, insulin, HbA1c, lipid profile, and serum adipokine levels were measured. Insulin resistance was estimated using the HOMA-IR index, while subclinical atherosclerosis was evaluated by carotid intima-media thickness (CIMT) using B-mode ultrasonography. Results: Mean HOMA-IR was 4.1 ± 1.6, and 62% of participants had CIMT ≥ 0.8 mm. Adiponectin levels were significantly reduced (4.6 ± 1.0 µg/mL), while leptin (18.7 ± 6.9 ng/mL), resistin (13.2 ± 3.6 ng/mL), and visfatin (36.9 ± 8.3 ng/mL) were elevated. Adiponectin correlated inversely with HOMA-IR (r = –0.44; p = 0.002) and CIMT (r = –0.36; p = 0.008), whereas resistin and visfatin showed positive correlations with both insulin resistance and CIMT (p < 0.01). Conclusion: Adipokine imbalance plays a critical role in the development of insulin resistance and early atherosclerosis in prediabetic individuals. These markers may serve as early predictors of cardiometabolic risk, warranting their inclusion in routine prediabetes screening to enable timely intervention and prevention of disease progression. Keywords: Prediabetes, Insulin resistance, Adipokines, Adiponectin, Leptin, Resistin, Visfatin, HOMA-IR, CIMT, Atherosclerosis